ANALISA PUTUSAN SENGKETA PILIHAN HUKUM WARIS - Bambang Yunarko (Institute for Research and Community Services (LPPM) of Wijaya Kusuma Surabaya University, 2005)
In course of analysis and creation punish for casa case which not yet there is its law order judge is obliged to dig the law values which live and looked after its midst goodness is its society Law values which live that for example: values of religion teaching, mores values which still be looked after a goodness, cultural and mount the society intelligence, social and economic circumstance of society.